Density-dependent dispersal in multiple species metapopulations - Jacques A. L. Silva; Flávia T. Giordani (Mathematical Biosciences and Engineering)
A multiple species metapopulations model with density-dependent dispersal is presented. Assuming the network configuration matrix to be diagonizable we obtain a decoupling of the associated perturbed system from the homogeneous state. It was possible to analyze in detail the instability induced by the density-dependent dispersal in two classes of $k$-species interaction models: a hierarchically organized competitive system and an age-structured model.